Clinical Evaluation by Means of Radiopaque Markers of Colonic Transit after Low Anterior Resection of Cancer - Morita, T.; Konn, M.; Nakamura, F. (Nippon Daicho Komonbyo Gakkai Zasshi, 1995)
Defecation problems observed after low anterior resection (LAR) of cancer included abnormally frequent stool passages, severe constipation and so on. As various motor conditions of the colonic segment above the anastomosis were thought to be causative, we evaluated colonic transit by using radiopaque markers administered per os. The examined subjects consisted of 37 patients within 1 month and 26 patients no less than 1 year after LAR, as well as 26 controls who had a normal bowel habit. The total transit time was 29.8±3.2 h for the controls and 41.1±1.7h for all the LAR patients (p<0.05). The total transit time was longer in both early-and late-postoperative LAR patients than in the control subjects. In most (90%) of the patients, the markers were retained in those having anastomosis. The patients undergoing bilateral pelvic autonomic nerve preservation had a shorter transit time than those undergoing unilateral nerve preservation. Colonic motor dysfunction after LAR was thought to be incurred by impairment of the pelvic autonomic (parasympathetic) nerve, i. e., the pelvic plexus or rectal branches arising from it.